The Effect of Sensory Marketing, Brand Experience, Brand Image, and Perceived Service Quality on Brand Loyalty with Customer Satisfaction as an Intervening Variable (Study Conducted on Luxury Brand Product Consumers): A Conceptual Paper - Adib Alfikry; Arry Widodo; Anita Silvianita; Nurafni Rubiyanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Luxury brands, epitomes of exclusivity and quality, thrive on their ability to evoke desire and loyalty among consumers. This study delves into the dynamics of brand loyalty within the context of sensory marketing, brand experience, brand image, and perceived service quality, with customer satisfaction acting as an intervening variable. Drawing on a rich literature review, this research aims to unravel the intricate relationships among these constructs in the luxury brand market of Indonesia. Through a quantitative research approach and purposive sampling technique, data will be collected to empirically test the hypothesized relationships. The study hypothesizes direct impacts of sensory marketing, brand experience, brand image, and perceived service quality on brand loyalty, as well as indirect effects mediated by customer satisfaction. By shedding light on these relationships, this research endeavors to contribute to a deeper understanding of consumer behavior in the luxury brand sector and provide valuable insights for marketers aiming to foster brand loyalty in this competitive market landscape